1976
DOI: 10.1677/joe.0.0680013
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Carp Interrenal Function by Adrenocorticotrophin

Abstract: The effect of ACTH on cortisol concentration in the plasma of the carp has been studied; cortisol was determined using a competitive protein-binding radioassay. Blood was sampled at 12.00 h (the diurnal minimum) by cardiac puncture. The plasma cortisol level of undisturbed carp (blood obtained 1--3 min after netting) was 16 +/- 14 (S.E.M.) ng/ml. One hour after injection of ACTH (1-0 i.u./100 g body wt., i.m.) the level of cortisol increased to 415 +/- 62 ng/ml and reached a maximum of 656 +/- 62 ng/ml after 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…), the few data available for carp suggest that the cortisol response to stress observed during the present study is characteristic of that observed in carp under a variety of stressful conditions. Both baseline pre-stress levels and levels of cortisol observed following capture in the present study are similar to those measured in carp before and following forced swimming (Leloup-Hatey, 1960), handling (Ilan & Yaron, 1976) and transport (Davis & Parker, 1976). The magnitude and duration of the response to capture stress in the present study is also very similar to that observed in carp exposed to acid stress (van Dijk et al, 1993) in which cortisol levels rose from approximately 35 ng ml -1 prior to the onset of stress to peak at approximately 370 ng ml -1 within four hours before returning to baseline within 24 hours.…”
Section: Effects Of Capture and Confinement On Plasma Cortisol Levelssupporting
confidence: 82%
“…), the few data available for carp suggest that the cortisol response to stress observed during the present study is characteristic of that observed in carp under a variety of stressful conditions. Both baseline pre-stress levels and levels of cortisol observed following capture in the present study are similar to those measured in carp before and following forced swimming (Leloup-Hatey, 1960), handling (Ilan & Yaron, 1976) and transport (Davis & Parker, 1976). The magnitude and duration of the response to capture stress in the present study is also very similar to that observed in carp exposed to acid stress (van Dijk et al, 1993) in which cortisol levels rose from approximately 35 ng ml -1 prior to the onset of stress to peak at approximately 370 ng ml -1 within four hours before returning to baseline within 24 hours.…”
Section: Effects Of Capture and Confinement On Plasma Cortisol Levelssupporting
confidence: 82%
“…Since the interrenal cells comprise only a small fraction of the total mass of the head kidneys in fish and cortisol content of head kidneys are not in correlation with the weight of the organ (Ilan & Yaron, 1976) there was no point in adjusting the units of cortisol output to the exact weight of the superfused tissue. The results were thus expressed as the rate of cortisol output from four pairs of head kidneys, assuming that the capacity to secrete cortisol in any pool of head kidneys taken from four fish would be similar.…”
Section: Methodsmentioning
confidence: 99%
“…2A, 3). This comparison may indicate that although some endocrine parameters in the carp, such as cortisol level, may change drastically due to handling stress (Ilan and Yaron 1976) other para-meters, such as GTH or estradiol, may not change appreciably during the first few hours of stress.…”
Section: Annual Cyclementioning
confidence: 99%